A resource-based analysis of the Gonzaga University men’s basketball program - Kenneth S. Anderson; G. Eddy Birrer (Journal of Applied Sports Management, 2011)
In recent years, the Resource-Based View (RBV) of firms has been applied to strategic management in the context of sport. Numerous studies have examined the relationship between human resource management and athletic performance, as well as success in sport sponsorship. Other studies employed the RBV in the context of professional sports franchises and a major NCAA athletic program. This paper builds on previous research by using the RBV to show how the effective management of a strategic resource has led to a sustained competitive advantage for the Gonzaga University men’s basketball program. The key resource of the Gonzaga program is identified and evaluated in the context of the RBV, and the strategic decisions made to manage that resource and ultimately create a sustainable competitive advantage are discussed.
Keywords: Resource-based view of Organizations; Gonzaga men’s basketball; strategic management; VRIO Framework; NCAA Men’s Sweet Sixteen